Social capital and corporate resilience: The case of small and medium enterprises in Vietnam - Dinh, Hien Thi Thu; Nguyen, Quyen Le Hoang Thuy To; Nguyen, Phong Thanh (International Journal of Management and Sustainability, 2024)
This study aims to investigate the role of social capital in fortifying resilience within Vietnam’s SMEs, in the context of global and domestic volatility, uncertainty, complexity, and ambiguity coupled with resource constraints. Employing quantitative data analysis, the research performs a survey of 500 SMEs located in three regions, including the North, Central, and South of Vietnam. Simple random sampling strategy is applied based on the list of SMEs. Questionnaires have been sent to the representatives of the SMEs management board after being contacted and confirmed the voluntary participation of the survey. Using the PLS-SEM technique, a variance-based approach is conducted. The findings demonstrate the positive influence of both external and internal social capital on distinct aspects of resilience. Specifically, external social capital significantly enhances flexibility and adaptability, while internal social capital correlates with agility, flexibility, and anticipatory capability. These results provide the scientific groundwork for effectively harnessing social capital to augment SMEs resilience in Vietnam. Understanding the impact of social capital on resilience offers practical guidance for policymakers, business owners, and practitioners in shaping strategies and policies to fortify SMEs against the challenges of the dynamic business environment. Furthermore, by contributing insights into the relationship between social capital and SMEs resilience, this research enriches discussions on SMEs development and resilience, thereby fostering sustainable progress in Vietnam.